Oxidative Stress and Bronchial Asthma in Children—Causes or Consequences? - Jesenak, Milos; Zelieskova, Maria; Babusikova, Eva (Frontiers in Pediatrics, 2017)
Bronchial asthma is one of the most common chronic inflammatory diseases of the airways. In the pathogenesis of this disease, the interplay among the genes, intrinsic, and extrinsic factors are crucial. Various combinations of the involved factors determine and modify the final clinical phenotype/endotype of asthma. Oxidative stress results from an imbalance between the production of reactive oxygen species and reactive nitrogen species and the capacity of antioxidant defense mechanisms. It was shown that oxidative damage of biomolecules is strongly involved in the asthmatic inflammation. It is evident that asthma is accompanied by oxidative stress in the airways and in the systemic circulation. The oxidative stress is more pronounced during the acute exacerbation or allergen challenge. On the other hand, the genetic variations in the genes for anti-oxidative and pro-oxidative enzymes are variably associated with various asthmatic subtypes. Whether oxidative stress is the consequence of, or the cause for, chronic changes in asthmatic airways is still being discussed. Contribution of oxidative stress to asthma pathology remains at least partially controversial, since antioxidant interventions have proven rather unsuccessful. According to current knowledge, the relationship between oxidative stress and asthmatic inflammation is bidirectional, and genetic predisposition could modify the balance between these two positions—oxidative stress as a cause for or consequence of asthmatic inflammation.